Investigating Various Thresholds as Immunohistochemistry Cutoffs for Observer Agreement. Issue 9 (October 2017) - Ali, Asif; Bell, Sarah; Bilsland, Alan; Slavin, Jill; Lynch, Victoria; Elgoweini, Maha; Derakhshan, Mohammad H.; Jamieson, Nigel B.; Chang, David; Brown, Victoria; Denley, Simon; Orange, Clare; et al.
Abstract : Background: Clinical translation of immunohistochemistry (IHC) biomarkers requires reliable and reproducible cutoffs or thresholds for interpretation of immunostaining. Most IHC biomarker research focuses on the clinical relevance (diagnostic, prognostic, or predictive utility) of cutoffs, with less emphasis on observer agreement using these cutoffs. From the literature, we identified 3 commonly used cutoffs of 10% positive epithelial cells, 20% positive epithelial cells, and moderate to strong staining intensity (+2/+3 hereafter) to use for investigating observer agreement. Materials and Methods: A series of 36 images of microarray cores stained for 4 different IHC biomarkers, with variable staining intensity and percentage of positive cells, was used for investigating interobserver and intraobserver agreement. Seven pathologists scored the immunostaining in each image using the 3 cutoffs for positive and negative staining. Kappa (κ) statistic was used to assess the strength of agreement for each cutoff. Results: The interobserver agreement between all 7 pathologists using the 3 cutoffs was reasonably good, with mean κ scores of 0.64, 0.59, and 0.62, respectively, for 10%, 20%, and +2/+3 cutoffs. A good agreement was observed for experienced pathologists using the 10% cutoff, and their agreement was statistically higher than for junior pathologists ( P =0.02). In addition, the mean intraobserver agreement for all 7 pathologists using the 3 cutoffs was reasonably good, with mean κ scores of 0.71, 0.60, and 0.73, respectively, for 10%, 20%, and +2/+3 cutoffs. For all 3 cutoffs, a positive correlation was observed with perceived ease of interpretation ( P <0.003). Finally, cytoplasmic-only staining achieved higher agreement using all 3 cutoffs than mixed staining patterns. Conclusions: All 3 cutoffs investigated achieve reasonable strength of agreement, modestly decreasing interobserver and intraobserver variability in IHC interpretation. These cutoffs have previously been used in cancer pathology, and this study provides evidence that these cutoffs can be reproducible between practicing pathologists. Abstract : Supplemental Digital Content is available in the text.